The Effect of Scramble Game Towards the Ability of Composing Sentences for Students with Intellectual Disability - Noverita Surya Dewi; Agung Kurniawan (Department of Special Education, 2017)
Children with intellectual disability have limitations in language acquisition mainly in processing vocabulary that is less functioning as it is expected, that is why they fell difficulty in preparing sentence. The purpose of this study was to describe the effects of the scramble games toward capability of sentence composition for students with intellectual disability. The method used is a quasi-experimental design with time series design. This study showed there was a difference capability of sentence composition for students with intelllectual disability before and after treatment with scramble game. It is shown from the results of t arithmetic < t table at significant level of 0.05 is 0 <1. The conclusion of this study was the scramble game affect toward capability of sentence composition for students with intellectual disability